2014
DOI: 10.1016/j.dcn.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Girls’ challenging social experiences in early adolescence predict neural response to rewards and depressive symptoms

Abstract: Developmental models of psychopathology posit that exposure to social stressors may confer risk for depression in adolescent girls by disrupting neural reward circuitry. The current study tested this hypothesis by examining the relationship between early adolescent social stressors and later neural reward processing and depressive symptoms. Participants were 120 girls from an ongoing longitudinal study of precursors to depression across adolescent development. Low parental warmth, peer victimization, and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 52 publications
(83 reference statements)
11
101
1
Order By: Relevance
“…Whereas some studies relied exclusively on the Baron and Kenny approach of mediation testing (1986) where mediation is inferred from comparing direct effect sizes with and without controlling for the mediating variable, studies increasingly used Hayes' well-documented and freely available SPSS macro PROCESS (e.g., Casement et al 2014;Guarneri-White et al 2015;Hamlat et al 2015;Mathieson et al 2014). Such novel approaches are needed to estimate possible double-and multiple-mediation, as are larger sample sizes than used in some of the studies reviewed here (e.g., Baker and Bugay 2011;Espinoza 2015;Giannotta et al 2012;Guarneri-White et al 2015;Harper 2012;Jenkins and Demaray 2015, who all used samples smaller than n = 200).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies relied exclusively on the Baron and Kenny approach of mediation testing (1986) where mediation is inferred from comparing direct effect sizes with and without controlling for the mediating variable, studies increasingly used Hayes' well-documented and freely available SPSS macro PROCESS (e.g., Casement et al 2014;Guarneri-White et al 2015;Hamlat et al 2015;Mathieson et al 2014). Such novel approaches are needed to estimate possible double-and multiple-mediation, as are larger sample sizes than used in some of the studies reviewed here (e.g., Baker and Bugay 2011;Espinoza 2015;Giannotta et al 2012;Guarneri-White et al 2015;Harper 2012;Jenkins and Demaray 2015, who all used samples smaller than n = 200).…”
Section: Discussionmentioning
confidence: 99%
“…Quite different from these mostly questionnaire based studies is a neuroimaging study by Casement et al (2014), who showed differences between victimized and non-victimized girls in activation of the medial prefrontal cortex, which is implicated in memory and decision making. The authors had hypothesized that individual response variation in this area would be related to depression, thus potentially constituting a mediating pathway between peer victimization and internalizing problems, but explicit mediation tests did not support this pathway.…”
Section: Mediators On Associations Between Peer Victimization and Intmentioning
confidence: 99%
“…At this age they begin to attach great importance to friendship bound together by common interests. In this respect, Casement et al (2014) remarked that for adolescents, their relationships with parents and peers are a crucial factor. Along the same line, Guthrie et al (1998) showed that reading motivation for social interaction is very important aspect.…”
Section: Students' Motivation To Readmentioning
confidence: 99%
“…4 Almost 20% of those who suffer depression during their lifetime have experienced the disorder when they were 12 to 19 years old. 5 According to studies conducted in the recent decade, the degree of depression among adolescents has been reported to range from 8% to 20%. 4 According to a study performed by Nair, it was indicated that 3% of adolescents aged 13 to 19 suffer depression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in some other studies, it was reported that girls suffer depression twice as many as boys. 1,5,[8][9][10] Given the fact that it will lead to disorders in a broad variety of social, educational, and professional performance, prevalence of depression is required to be significantly taken into consideration. Various studies have shown an estimated depression prevalence rate ranging from 10% to 30%.…”
Section: Introductionmentioning
confidence: 99%